2008
DOI: 10.1080/17450390802027494
|View full text |Cite
|
Sign up to set email alerts
|

Methionine, folic acid and vitamin B12in growing-finishing pigs: Impact on growth performance and meat quality

Abstract: Growth performance, metabolic variables, and meat quality were measured in 78 growing-finishing pigs using supplements of 0 (C), or 0.2% of DL-methionine (M), and three combinations of folic acid [mg/kg] and cyanocobalamin [microg/kg], respectively 0 and 0 (V0), 10 and 25 (V1), and 10 and 150 (V2) in a 2 x 3 factorial arrangement. Feed conversion was lower (p = 0.05) in M than in C pigs during the growing period (0-4 weeks). Both V1 and V2 treatments increased plasma vitamin B12 (p < 0.01) and decreased plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…A major metabolic route for disposal of Hcy is remethylation where B 12 -dependent methionine synthase transfers a methyl group from 5-methyl-tetrahydrofolate for regeneration of methionine (Bässler, 1997). In pigs, plasma Hcy (pHcy) responds to folic acid and/or B 12 at University of Cambridge on December 3, 2014 www.journalofanimalscience.org Downloaded from supplements but minimum values remain high (> 15 µM) as compared to other species (< 10 µM) (Simard et al, 2007;Giguère et al, 2008). To our knowledge, it is not known yet if such greater pHcy is harmful for piglets.…”
Section: Introductionmentioning
confidence: 90%
“…A major metabolic route for disposal of Hcy is remethylation where B 12 -dependent methionine synthase transfers a methyl group from 5-methyl-tetrahydrofolate for regeneration of methionine (Bässler, 1997). In pigs, plasma Hcy (pHcy) responds to folic acid and/or B 12 at University of Cambridge on December 3, 2014 www.journalofanimalscience.org Downloaded from supplements but minimum values remain high (> 15 µM) as compared to other species (< 10 µM) (Simard et al, 2007;Giguère et al, 2008). To our knowledge, it is not known yet if such greater pHcy is harmful for piglets.…”
Section: Introductionmentioning
confidence: 90%
“…In carcass, vitamin B 12 concentration and total content increased (P < 0.01) with the dietary intake of vitamin B 12 (Table 2). Giguère et al (2008) reported that vitamin B 12 concentrations in LM of 10-wk-old pigs were 3.7 and 4.1 ng/g after a long-term (8 wk) dietary supplementation of cyanocobalamin at 25 and 150 μg/ kg, respectively. The present carcass values included mainly muscles but also other metabolic pools such as blood, bone marrow, and other organs that might have contributed to greater vitamin B 12 concentrations compared with Giguère et al (2008) because, according to Scheid and Schweigert (1954), concentrations of vitamin B 12 in kidneys, pancreas, spleen, heart, brain, and lungs of pigs vary between 21 and 165 ng/g.…”
Section: Trialmentioning
confidence: 99%
“…Typical amounts used by the feed industry range between 20 and 30 μg/kg (BASF, 2001). Recently, House and Fletcher (2003) and Giguère et al (2008) showed that supplements of 35 and 25 μg/kg of vitamin B 12 would be required in weaner or grower-finisher pigs, respectively. In gilts, Simard et al (2007) showed that when dietary vitamin B 12 increased 10 times, from 20 to 200 μg/kg, vitamin B 12 in blood plasma was doubled.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the potential for enriching the folate content of foods of animal origin with high levels of folic acid supplementation in feed. The folate content of muscle was not significantly increased in pigs fed 10 mg/kg folic acid for 28 days when compared with unsupplemented controls (Giguère et al, 2008). Also, no significant increase compared with unsupplemented controls was observed in the liver of laying hens fed up to 10 mg/kg for up to 56 days (Bunchasak and Kachana, 2009;Tactacan et al, 2010) or in the thigh muscle and liver of chickens for fattening fed 2-32 mg/kg for 42 days: although a numerical increase was observed in breast muscle following supplementation with 2 mg folic acid/kg compared with the unsupplemented group (159 vs 101 μg/kg), no further increase was observed at higher doses .…”
Section: Absorption Distribution Metabolism and Excretion Of Folic mentioning
confidence: 78%
“…The folate content of muscle was not significantly increased in pigs fed 10 mg/kg folic acid for 28 days when compared with unsupplemented controls (Giguère et al, 2008). The folate content of muscle was not significantly increased in pigs fed 10 mg/kg folic acid for 28 days when compared with unsupplemented controls (Giguère et al, 2008).…”
Section: Absorption Distribution Metabolism and Excretion Of Folic mentioning
confidence: 91%